2016
DOI: 10.1111/inr.12300
|View full text |Cite
|
Sign up to set email alerts
|

Internationally educated nurses’ reflections on nursing communication in Canada

Abstract: Clear communication from regulators about English language and nursing communication requirements during the pre-arrival period is recommended. If bridging education is required, these programs need to be designed to address English language competency and nursing communication skills of non-native English speakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
(52 reference statements)
0
35
0
1
Order By: Relevance
“…Comparing IENs' perceptions by source country highlights the heterogeneity of the IEN population as a factor that influences the type of support required to successfully integrate into the destination country's nursing workforce (Lum et al. ). This evidence can help policymakers tailor support and educational programme curricula to address IENs' unique upgrading needs which may be greater for IENs from countries where the education system, professional practise models and healthcare systems differ greatly from the destination country.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing IENs' perceptions by source country highlights the heterogeneity of the IEN population as a factor that influences the type of support required to successfully integrate into the destination country's nursing workforce (Lum et al. ). This evidence can help policymakers tailor support and educational programme curricula to address IENs' unique upgrading needs which may be greater for IENs from countries where the education system, professional practise models and healthcare systems differ greatly from the destination country.…”
Section: Discussionmentioning
confidence: 99%
“…Increased transparency and communication about the complex process can decrease uncertainty and frustration among IENs and stakeholders (Lum et al. ). Sharing timeline analyses helped stakeholders understand that often delays occurred during parts of the process over which CARNA had no control, for example time to complete courses.…”
Section: Discussionmentioning
confidence: 99%
“…Regulators are responsible for quality, safe nursing care and therefore must ensure that IENs have equivalent competencies to Canadian‐educated nurses (Sherwood & Shaffer ) using evidence‐informed, fair and transparent registration processes (Lum et al. ; Ohr et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that internationally trained healthcare professionals, including pharmacists, face numerous challenges in their adaptation process into the host heal the care system . Where English is a foreign language, the literature on ITNs and ITDs has identified language and communication barriers as a root cause for issues related to adaptation and integration of these healthcare professionals into the workforce, with some studies raising the potential impact of communication problems on patient safety and quality of care …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Where English is a foreign language, the literature on ITNs and ITDs has identified language and communication barriers as a root cause for issues related to adaptation and integration of these healthcare professionals into the workforce, with some studies raising the potential impact of communication problems on patient safety and quality of care. [19][20][21][22][23][24][25] Only one qualitative study undertaken in GB has explored communicative proficiency of ITPs and its potential impact on patient safety. [20] This study showed that, besides inadequate oral proficiency in English, different dialects, use of idioms and colloquial language could cause difficulties to ITPs.…”
Section: Introductionmentioning
confidence: 99%